2004
DOI: 10.1158/0008-5472.can-04-1476
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous Mutations in Digestive Tract of Old Mice Show Tissue-Specific Patterns of Genomic Instability

Abstract: In an attempt to evaluate the possible role of mutations in the agedependent increase of tumor incidence, we studied the mutational burden that accumulates in the aging process in different parts of the digestive tract in mice. The mutations were monitored in lacZ genes integrated in the mouse genome. The digestive tract was divided into the esophagus, stomach, proximal, medial, and distal part of the small intestine, and the colon. Epithelial tissues were separated from these tissues with the exception of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
15
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 33 publications
3
15
0
Order By: Relevance
“…Similar studies have been done with 10 other tissues and they are summarized in Fig. 3 (17,18). Mutants accumulate most rapidly in the epithelial tissues of the small and large intestine resulting in a 5-to 6-fold increase in mutant frequencies during 2 to 23 months of age.…”
Section: Spontaneous Mutations In Newborn and Young Mice Show Little supporting
confidence: 67%
See 3 more Smart Citations
“…Similar studies have been done with 10 other tissues and they are summarized in Fig. 3 (17,18). Mutants accumulate most rapidly in the epithelial tissues of the small and large intestine resulting in a 5-to 6-fold increase in mutant frequencies during 2 to 23 months of age.…”
Section: Spontaneous Mutations In Newborn and Young Mice Show Little supporting
confidence: 67%
“…Epithelial tissue in the proximal small intestine in old mice revealed a rise of G:C to T:A events. A similar tendency was also observed in the medial part of the small intestine (17). Since this type of mutation is known to be induced by oxidized guanine (8OHG), a possible cause could be an elevated level of this type of damage in the tissue, or an insu‹cient level of activity of the repair gene Ogg1 which is responsible for the removal of 8OHG (26).…”
Section: What Is the Cause Of Tissue-speciˆcity?supporting
confidence: 55%
See 2 more Smart Citations
“…Moreover, the age of mice examined would also contribute to the difference because we found no histologic abnormalities in 12-month-old mice but a significant number of tumors in 18-month-old mice (19). It has been reported that the incidence of G:C to T:A transversions increases significantly in the intestines of older mice compared with younger mice (26,27). Because this transversion is mainly caused by oxidative DNA damage such as 8-oxoG lesions, these observations indicate that the mutations caused by this damage would tend to accumulate in the intestines during the course of aging.…”
Section: Discussionmentioning
confidence: 70%